185k views
4 votes
If the function f(x)= 2x – 3 and g(x) = 3/2x + 1 then which of the following is a true statement?

f(0) > g(0)
f(8) = g(8)
f(2) = g(2)
g(4) < f(4)

User Insign
by
4.5k points

1 Answer

4 votes

Answer:

f(8) = g(8)

Explanation:

Given

f(x)= 2x – 3 and g(x) = 3/2x + 1

f(0)= 2(0)-3

f(0) = -3

g(0) = 3/2(0)+1

g(0) = 0+1

g(0) = 1

Hence since -3 < 1, this means that f(0)<g(0)

Also;

f(8)= 2(8)-3

f(8) = 16-3

f(8) = 13

g(8) = 3/2(8)+1

g(8) =12+1

g(8) = 13

This shows that g(8) = g(8)

Hence g(8) = g(8) is a true statement

User George Ninan
by
4.3k points